COLONIAL LEGACY AND PUBLIC POLICY DYNAMICS IN THE PERSPECTIVE OF HISTORICAL-COMPARATIVE ANALYSIS OF PAPUAN DEVELOPMENT - Dorhea Renyaan; Kristofol Kendi, Ibrahim (International Journal of Multidisciplinary Reseach, 2026)
This study explores the relationship between colonial legacy and public policy dynamics in Papua to understand the roots of development inequality and social conflicts that still occur today. Papua, with its long history of Dutch colonialism and post-integration administrative transition to Indonesia, experienced the formation of social, political, and economic structures rooted in the colonial system. Through a literature study method with a historical-comparative approach, this study analyzed 150 publications using the PRISMA framework and CASP instruments to ensure the quality and transparency of the analysis. The results show that colonial legacy creates a centralistic, top-down, and exploitative public policy pattern, where indigenous peoples are often marginalized in the development process. This inequality is reflected in the low Human Development Index (HDI) of Papua and the high poverty rate despite the implementation of Special Autonomy with a large allocation of funds. Theoretically, this study integrates postcolonial theory, dependency theory, and institutional path dependence to explain the continuity between colonialism and contemporary policy. The findings show that the colonial logic still operates in its modern form through hierarchical bureaucracy and development policies that ignore the local context. The novelty of this research lies in the use of historical-comparative analysis in the study of Papuan public policy, which highlights the importance of decolonization of governance and cognitive justice for indigenous peoples. Further research opportunities include studies on the decolonization of regional public policies through strengthening local institutions, longitudinal analysis of the effectiveness of Papuan Special Autonomy, and comparative studies between postcolonial regions in Eastern Indonesia. In addition, future research can examine the participation of indigenous peoples in policy processes, analysis of colonial discourse in government documents, as well as the relationship between colonial heritage and ecological inequality in Papua. The integration of postcolonial perspectives in public policy education is also an important agenda to build a decolonial paradigm in the formulation of policies that are more equitable, participatory, and contextual for the Papuan people.